Modular ABM development for improved dissemination and training. (November 2015) - Bell, Andrew R.; Robinson, Derek T.; Malik, Ammar; Dewal, Snigdha
Abstract: Agent-based models (ABMs) have become an important tool for advancing scientific understanding in a variety of disciplines and more specifically have contributed gains to natural resource management in recent decades. However, a key challenge to their utility is the lack of convergence upon a common set of assumptions for representing key processes (such as agent decision structure), with the outcome that published ABM tools are rarely (if ever) used beyond their original development team. While a number of ABM frameworks are publicly available for use, the continued development of models from scratch is a signal of the continuing difficulty in capturing sufficient modeling flexibility in a single package. In this study we examine ABM sharing by comparing co-citation networks from several well-known ABM frameworks to those used in the land-use change modeling community. We then outline a different publication paradigm for the ABM community that could improve the sharing of model structure and help move toward convergence on a common set of tools and assumptions. Highlights: Gaps in the reuse and publication of agent-based modeling primitives are exposed. Coauthorship networks of statistical versus agent models differ substantially. Examples of agent-based modeling primitives and options for research are provided.